Catheter ablation of anteroseptal accessory pathways from the aortic cusps: A case series and a review of the literature. Issue 6 (19th April 2016) - Letsas, Konstantinos P.; Efremidis, Michael; Vlachos, Konstantinos; Georgopoulos, Stamatis; Karamichalakis, Nikolaos; Saplaouras, Athanasios; Xydonas, Sotirios; Valkanas, Kosmas; Sideris, Antonios
Abstract: Data regarding catheter ablation of anteroseptal accessory pathways through the aortic cusps are limited. We describe two cases of true para‐Hisian accessory pathways successfully ablated from the aortic cusps (right coronary cusp and non‐coronary cusp, respectively) along with a review of the current literature. Due to the close proximity to the atrioventricular node and the high risk of complication, mapping of the aortic cusps should always be considered in the case of anteroseptal accessory pathways. Anteroseptal accessory pathways can be safely and effectively ablated from the aortic cusps with good long‐term outcomes.